A fast and sensitive method for the continuous in situ determination of dissolved methane and its δ13C‐isotope ratio in surface waters. (27th April 2018) - Hartmann, Jan F.; Gentz, Torben; Schiller, Amanda; Greule, Markus; Grossart, Hans‐Peter; Ionescu, Danny; Keppler, Frank; Martinez‐Cruz, Karla; Sepulveda‐Jauregui, Armando; Isenbeck‐Schröter, Margot
Abstract: A fast and sensitive method for the continuous determination of methane (CH4 ) and its stable carbon isotopic values (δ 13 C‐CH4 ) in surface waters was developed by applying a vacuum to a gas/liquid exchange membrane and measuring the extracted gases by a portable cavity ring‐down spectroscopy analyser (M‐CRDS). The M‐CRDS was calibrated and characterized for CH4 concentration and δ 13 C‐CH4 with synthetic water standards. The detection limit of the M‐CRDS for the simultaneous determination of CH4 and δ 13 C‐CH4 is 3.6 nmol L −1 CH4 . A measurement precision of CH4 concentrations and δ 13 C‐CH4 in the range of 1.1%, respectively, 1.7‰ (1 σ ) and accuracy (1.3%, respectively, 0.8‰ [1 σ ]) was achieved for single measurements and averaging times of 10 min. The response time τ of 57 ± 5 s allow determination of δ 13 C‐CH4 values more than twice as fast than other methods. The demonstrated M‐CRDS method was applied and tested for Lake Stechlin (Germany) and compared with the headspace‐gas chromatography and fast membrane CH4 concentration methods. Maximum CH4 concentrations (577 nmol L −1 ) and lightest δ 13 C‐CH4 (−35.2‰) were found around the thermocline in depth profile measurements. The M‐CRDS‐method was in good agreement with other methods. Temporal variations in CH4 concentration and δ 13 C‐CH4 obtained in 24 h measurements indicate either local methane production/oxidation or physical variations in the thermocline. Therefore, these results illustrate the need of fast and sensitive analyses to achieve a better understanding of different mechanisms and pathways of CH4 formation in aquatic environments.